Development and validation of a rapid ultra high performance liquid chromatography with tandem mass spectrometry method for the simultaneous determination of darunavir, ritonavir, and tenofovir in human plasma: Application to human pharmacokinetics. Issue 15 (18th June 2015) - Reddy, Ambavaram Vijaya Bhaskar; Jaafar, Jafariah; Aris, Azmi Bin; Majid, Zaiton Abdul; Umar, Khalid; Talib, Juhaizah; Madhavi, Gajulapalle
<x xml:space="preserve">Abstract</x> A sensitive ultra high performance liquid chromatography with tandem mass spectrometry method was developed for the simultaneous determination of darunavir, ritonavir and tenofovir in human plasma. Sample preparation involved a simple liquid–liquid extraction using 200 μL of human plasma extracted with methyl tert‐butyl ether for three analytes and internal standard. The separation was accomplished on an Acquity UPLC BEH C18 (50 mm x 2.1 mm, 1.7 μm) analytical column using gradient elution of acetonitrile/methanol (80:20, v/v) and 5.0 mM ammonium acetate containing 0.01% formic acid at a flow rate of 0.4 mL/min. The linearity of the method ranged between 20.0 and 12 000 ng/mL for darunavir, 2.0 and 2280 ng/mL for ritonavir, and 14.0 and 1600 ng/mL for tenofovir using 200 μL of plasma. The method was completely validated for its selectivity, sensitivity, linearity, precision and accuracy, recovery, matrix effect, stability, and dilution integrity. The extraction recoveries were consistent and ranged between 79.91 and 90.04% for all three analytes and internal standard. The method exhibited good intra‐day and inter‐day precision between 1.78 and 6.27%. Finally the method was successfully applied for human pharmacokinetic study in eight healthy male volunteers after the oral administration of 600 mg darunavir along with 100 mg ritonavir and 100 mg tenofovir as boosters.